Relative Validity and Reproducibility of a Dietary Screener Adapted for Use Among Pregnant Women in Dhulikhel, Nepal. (7th June 2021) - Tiderencel, Kelly; Shah, Krupali; Shrestha, Abha; Barrett, Emily S; Shrestha, Archana; Rawal, Shristi
Abstract: Objectives: Culturally appropriate dietary assessments are lacking in many low-income countries including Nepal. Here we examined the reproducibility and validity of a dietary screener which was translated and adapted to assess diet quality among pregnant Nepalese women. Methods: A pilot cohort of singleton pregnant women (N = 101; age 25.9 ± 4.1 years) was recruited from a tertiary, periurban hospital in Nepal. An adapted Nepali version of the PrimeScreen questionnaire, assessing weekly consumption frequency of 12 healthy and 9 unhealthy food groups, was administered twice and a month apart in both the 2 nd and 3 rd trimester. Up to four inconsecutive 24-hr dietary recalls (24-HDRs) were also completed each trimester and utilized as the reference method for validation. For each trimester, data from multiple 24-HDRs were averaged across days, and items were grouped to match the classification and the three weekly consumption categories (0–1, 2–3 or 4 + servings/week) of the 21 food groups represented on the PrimeScreen. Gwet's agreement coefficients (AC1) were used to evaluate the reproducibility and validity of the adapted PrimeScreen against the 24-HDRs in both 2 nd and 3 rd trimester. Results: In the 2 nd trimester, the adapted PrimeScreen demonstrated good to excellent reproducibility (AC1 > 0.6) for majority of the food groups; the reproducibility was moderate for eggs (AC1 = 0.4), and poor (AC1 < 0.4) for citrus fruits and leafy vegetables. In the 3 rd trimester, AC1 for reproducibility of the PrimeScreen ranged from 0.4 (moderate agreement) to 1 (excellent agreement), with values ≥0.6 for 90% of the items indicating good to excellent reproducibility for the majority of the food groups. Compared to 24-HDRs, the adapted PrimeScreen showed moderate to excellent validity (AC1 ≥ 0.4) for all food groups except for eggs and leafy vegetables in both the 2 nd and 3 rd trimester, and additionally citrus fruits and cruciferous vegetables in the 2 nd trimester alone. Classification into 3 consumption categories (0–1, 2–3 or 4 + servings/week) were consistent (percentage agreement > 80%) between the PrimeScreen and 24-HDR for 80% of the food groups in both 2 nd and 3 rd trimester. Conclusions: The adapted PrimeScreen questionnaire appears to be a reliable and valid instrument for assessing the dietary intake of most food groups among pregnant women in Nepal. Funding Sources: NIH/FIC.